PENGGUNAAN MULTIMEDIA PADA PEMBELAJARAN BAHASA ARAB DI MADRASAH ALIYAH MUALLIMIN DARUSSALAM MARTAPURA - Annisa Achla; Wahyuddin Wahyuddin; Ade Destri Deviana (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2022)
Abstract:Arabic subjects play an important role for students of Madrasah Aliyah. Based on initial observations in Madrasah Aliyah Muallimin Darussalam Martapura, student learning outcomes are classified as low and students' lack of interest in learning, it is necessary to improve teaching skills, especially in using multimedia. The use of multimedia can help the learning process more interesting. The purpose of this study was to identify the effectiveness of Arabic language education using multimedia as a facility to help students learn. The formulation of the problem includes student learning outcomes without multimedia and using multimedia, how effective is the use of multimedia, whether there is a significant effect between learning without using multimedia and using multimedia. The research technique in the form of data collection includes observation, interviews, documentation and tests. This type of research uses a quantitative approach with experimental procedures. The research subjects of class X students were 28 students. The results of the process research showed the results in the control group was 69.74 and the experimental group was 85.12, the difference between the two was 15.38. Evaluation on the U test is Zcount less than –Ztable- 62, 24 - 1, 75, then Ha can be accepted and Ho is rejected so that it has a significant impact on the learning process of the control group and the experimental group. On the other hand, the results of the learning evaluation tests in the control group 65, 75 and the experimental group 75, 90. For the U test calculation, Zcount is less than -ZTable-4, 02≤-2, 85 until Ha is acceptable and Ho is rejected until there is a significant impact.  Keywords: Arabic, Effectiveness, Multimedia. Abstrak:Mata pelajaran bahasa Arab berperan penting bagi siswa Madrasah Aliyah. Berdasarkan observasi awal di Madrasah Aliyah Muallimin Darussalam Martapura, hasil belajar siswa yang tergolong rendah serta kurangnya minat siswa dalam belajar, maka perlu meningkatkan keterampilan mengajar, khususnya dalam menggunakan multimedia. Penggunaan multimedia dapat membantu proses belajar lebih menarik. Tujuan penelitian ini buat mengenali keefektifan pendidikan bahasa Arab memakai multimedia selaku fasilitas menolong siswa dalam belajar. Rumusan masalah meliputi hasil belajar siswa tanpa multimedia dan menggunakan multimedia, seberapa efektif penggunaan multimedia, apakah terdapat pengaruh signifikan antara pembelajaran tanpa menggunakan multimedia dan menggunakan multimedia. Teknik penelitian berupa pengumpulan data meliputi observasi, wawancara, dokumentasi dan tes. Tipe riset memakai pendekatan kuantitatif dengan tata cara eksperimen. Subjek penelitian siswa kelas X berjumlah 28 siswa. Hasil penelitian proses menunjukkan hasil di kelompok kontrol 69,74 dan kelompok eksperimen 85,12, selisih antara keduanya 15,38. Evaluasi pada uji U merupakan Zhitung kurang dari –Ztabel- 62, 24 ≤ - 1, 75, maka Ha dapat diterima serta Ho ditolak hingga menimbulkan dampak signifikan pada proses belajar kelas kelompok kontrol dan kelompok eksperimen. Sebaliknya hasil tes evaluasi belajar pada kelompok kontrol 65, 75 dan kelompok eksperimen 75, 90 Bagi perhitungan uji U Zhitung kurang dari- ZTabel- 4, 02≤- 2, 85 hingga Ha dapat diterima serta Ho ditolak hingga terdapat dampak yang signifikan. Kata Kunci: Bahasa Arab, Efektivitas, Multimedia.